2022
DOI: 10.18287/jbpe22.08.040506
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamonds for Biomedical Applications – Features of Interaction with Blood Components and Behavior in the Circulatory System [Review]

Abstract: The development of the application of nanoparticles for biomedical research and theranostics in many cases involves the injection of nanoparticles into the bloodstream. The interaction of nanoparticles with blood components and the circulatory system is one of the key points of the relevant study or treatment. In this review, the interaction of diamond nanoparticles with blood in vivo and in vitro is considered in terms of the nanodiamonds safety and hematocompatibility and biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Viability studies on human ovary adenocarcinoma (SKOV-3) cells revealed no significant cytotoxic effect. This group presented in vivo longitudinal MRI monitoring experiments (7 T) for tracking cancer growth, morphology, and differentiation [31]. Subsequently, a second Gd-ND generation was designed through the grafting of Gd-DO3A-C 5 -COOH chelate (r 1 = 6.4 s −1 mM −1 , 1.41 T, 37 • C) onto amino-functionalized DNDs as aggregates [31].…”
Section: Nanoparticles Of Diamond (Nds)mentioning
confidence: 99%
See 2 more Smart Citations
“…Viability studies on human ovary adenocarcinoma (SKOV-3) cells revealed no significant cytotoxic effect. This group presented in vivo longitudinal MRI monitoring experiments (7 T) for tracking cancer growth, morphology, and differentiation [31]. Subsequently, a second Gd-ND generation was designed through the grafting of Gd-DO3A-C 5 -COOH chelate (r 1 = 6.4 s −1 mM −1 , 1.41 T, 37 • C) onto amino-functionalized DNDs as aggregates [31].…”
Section: Nanoparticles Of Diamond (Nds)mentioning
confidence: 99%
“…This group presented in vivo longitudinal MRI monitoring experiments (7 T) for tracking cancer growth, morphology, and differentiation [31]. Subsequently, a second Gd-ND generation was designed through the grafting of Gd-DO3A-C 5 -COOH chelate (r 1 = 6.4 s −1 mM −1 , 1.41 T, 37 • C) onto amino-functionalized DNDs as aggregates [31]. A two-fold Gd 3+ content increase (~1.5 µmol Gd /mg of DND aggregates) was obtained compared to the first generation.…”
Section: Nanoparticles Of Diamond (Nds)mentioning
confidence: 99%
See 1 more Smart Citation